A(n)=4+(n+1)(6)

Simple and best practice solution for A(n)=4+(n+1)(6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for A(n)=4+(n+1)(6) equation:


Simplifying
A(n) = 4 + (n + 1)(6)

Multiply A * n
nA = 4 + (n + 1)(6)

Reorder the terms:
nA = 4 + (1 + n)(6)

Reorder the terms for easier multiplication:
nA = 4 + 6(1 + n)
nA = 4 + (1 * 6 + n * 6)
nA = 4 + (6 + 6n)

Combine like terms: 4 + 6 = 10
nA = 10 + 6n

Solving
nA = 10 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
-6n + nA = 10 + 6n + -6n

Combine like terms: 6n + -6n = 0
-6n + nA = 10 + 0
-6n + nA = 10

Reorder the terms:
-10 + -6n + nA = 10 + -10

Combine like terms: 10 + -10 = 0
-10 + -6n + nA = 0

The solution to this equation could not be determined.

See similar equations:

| z^5=0 | | 15.35+10.25c=425.35 | | -3(4x+3)+4(6x+1)=43+4x | | (149-3x)=(5x+12) | | 1+14i= | | 5n^2-58n+80= | | 2x-6+2x-6+x+3+x+3=26 | | 3(-x-3)=4x-2(x+1) | | 25m+.45=40m+.25 | | t-(8*8+0.36)=0.5 | | 3(-x+3)=4x-2(x+1) | | 4t+9=8-13 | | -7.5+5.5(1+9d)=-17.5 | | 15.35+10.25c=353.6 | | 1.4n+4*4*4=85 | | 2m^2-7m+3= | | x^2-2x-240=0 | | 3x-35=128 | | -27.5+4c=-28.5-3y | | 99+x=189 | | 10x+20+12x=180 | | 13x+2=2x+2 | | 5x*8y=12 | | 52-3*7=62 | | 23.99x+120.84x=675.28 | | 3[2p-5]=33 | | 7.5(7y-5)=-28.5-3y | | 8-3a+8a-8b+3b= | | X*45=15 | | x-3+x+8=70 | | -15.5=-6(3.5k+6.5) | | -6w+15=51 |

Equations solver categories